Exoneree Engagement in Policy Reform Work: an Exploratory Study of the Innocence Movement Policy Reform Process - Konvisser, Zieva Dauber (Journal of contemporary criminal justice, 2017)
Through a lens of resilience and growth alongside continuing distress, this exploratory research study examines a convenience sample of exonerees and innocence movement personnel who are engaged in the policy reform process to understand how exoneree involvement may change exonerees themselves, the innocence movement, and possibly the criminal justice system. Data were collected through pre-questionnaires and semi-structured interviews, supplemented with archival material, and analyzed using a narrative approach. Findings emphasize both the personal and broader societal value of exoneree engagement in educating, generating awareness, and advocating about wrongful conviction and the power of having the human voice and face in front of legislators, the public, and the media—vividly portraying that “if they can do it to me, they can do it to anybody.” Findings also caution to be sensitive to where individuals may be in their lives and to honor their choices to engage or not.